2018
DOI: 10.1021/acs.analchem.8b04324
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time, Digital LAMP with Commercial Microfluidic Chips Reveals the Interplay of Efficiency, Speed, and Background Amplification as a Function of Reaction Temperature and Time

Abstract: Real-time, isothermal, digital nucleic acid amplification is emerging as an attractive approach for a multitude of applications including diagnostics, mechanistic studies, and assay optimization. Unfortunately, there is no commercially available and affordable real-time, digital instrument validated for isothermal amplification; thus, most researchers have not been able to apply digital, real-time approaches to isothermal amplification. Here, we generate an approach to real-time digital loop-mediated isotherma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 35 publications
(97 reference statements)
3
34
0
Order By: Relevance
“…We found that TTP can be heterogeneous while T m is constant (28.6 ± 8.9 min with 87.5 ± 0.2 • C), indicating that the same product may initiate at different times ( Figure 5F). This is consistent with our knowledge of the stochastic initiation of LAMP (23,(38)(39). Further, we observed some variability in the maximum rate despite similar T m (23.7 ± 6.8 RFU/30 s, with 87.5 ± 0.2 • C T m ), which indicates the same product may amplify at different velocities ( Figure 5G).…”
Section: Melting Temperature Differentiates Specific and Non-specificsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that TTP can be heterogeneous while T m is constant (28.6 ± 8.9 min with 87.5 ± 0.2 • C), indicating that the same product may initiate at different times ( Figure 5F). This is consistent with our knowledge of the stochastic initiation of LAMP (23,(38)(39). Further, we observed some variability in the maximum rate despite similar T m (23.7 ± 6.8 RFU/30 s, with 87.5 ± 0.2 • C T m ), which indicates the same product may amplify at different velocities ( Figure 5G).…”
Section: Melting Temperature Differentiates Specific and Non-specificsupporting
confidence: 91%
“….75 • C ( Figure 6E) and we observed better separation of specific and non-specific amplification than with Bst 2.0 ( Figure 6F and Supplementary Figure S8B). Both enzymes had highly variable TTP, which we have observed previously (23) and attribute to stochastic initiation of LAMP. Bst 2.0 had both earlier specific amplification and later non-specific amplification than Bst 3.0.…”
Section: Melting Temperature Differentiates Specific and Non-specificsupporting
confidence: 71%
See 2 more Smart Citations
“…One such isothermal amplification method, loop-mediated isothermal amplification (LAMP), provides specific and efficient amplification of target nucleic acids by targeting 8 unique sequences (Nagamine et al, 2002). Operable at a single temperature (most efficiently between 65 and 72 °C) (NEB, n.d.; Rolando et al, 2019), LAMP robustly amplifies even in the presence of complex sample matrices, further reducing sample processing and instrumentation requirements (Clayton et al, 2019;Mori and Notomi, 2009;Phillips et al, 2018). To expedite sample preparation steps, such as reverse transcription (RT) of HIV RNA targets, several groups have demonstrated that RT can be performed using the same assay conditions as LAMP (Curtis et al, 2012;Damhorst et al, 2015;Odari et al, 2015;Rudolph et al, 2015).…”
Section: Introductionmentioning
confidence: 99%